ONLINE MIND MAPS AS ONE OF THE MEANS OF MASTERING FOREIGN LANGUAGE VOCABULARY - Vishnyakova , E.A. (Scientific practical conference, 2025)
Structuring information is important when learning vocabulary in a foreign language. Using mind maps will help students navigate new vocabulary more easily. Online mind map platforms can make this task easier.